Go Home or Die Here : Violence, Xenophobia and the Reinvention of Difference in South Africa - Worby, Eric; Kupe, Tawana; Hassim, Shireen (Book collections on Project MUSE., 2008)
The xenophobic attacks that started in Alexandra, Johannesburg in May 2008 before quickly spreading around the country caused an outcry across the world and raised many fundamental questions: Of what profound social malaise is xenophobia - and the violence that it inspires - a symptom? Have our economic and political choices created new forms of exclusion that fuel anger and distrust? What consequences does the emergence of xenophobia hold for the idea of an equal, nonracial society as symbolised by a democratic South Africa? On 28 May 2008 the Faculty of Humanities in the University of the Witwatersrand, Johannesburg convened an urgent colloquium that focused on searching for short and long-term solutions. Nearly twenty individuals - mostly Wits academics from a variety of disciplines, but also two student leaders, a journalist and a bishop - addressed the unfolding violence in ways that were conversant with the moment, yet rooted in scholarship and ongoing research. Go Home or Die Here emanates directly from the colloquium. It hopes to make sense of the nuances and trajectories of building a democratic society out of a deeply divided and conflictual past, in the conditions of global recession, heightening inequalities and future uncertainty. The authors hoped to pose questions that would lead both to research and to more informed, reflective forms of public action. With extensive photographs by award-winning photographer Alon Skuy, who covered the violence for The Times newspaper, the volume is passionate and engaged, and aims to stimulate reflection, debate and activism among concerned members of a broad public.